Teachers Development Programs in Family and Everyday Life Skills in Saudi Arabia - Alharbi, Mashael (Universitas Majalengka, 2024)
Developing teacher training programs is one of the essential objectives of Saudi Arabia’s Vision 2030. This research highlighted one of the Ministry of Education's initiatives, the Optimum Utilization of Teaching Staff Project (OUTSP), to enhance teachers' knowledge and skills. This research focuses on the Family and Everyday Life Skills (FELS) program under (OUTSP). The study provided the results of 23 universities in 2021-2022 and 24 universities in 2022-2023 in more detail. For the data analysis, Microsoft Excel was used to show the results of the universities in different years. The results show that the universities' performances generally increased for both graduation classes, which could explain the increase in university performance. The research concludes that (FELS) as a program of the (OUTSP) project is an effective achievement for teachers' development through professional training program. The research further concludes that it is possible to provide adequate teacher training programs to teach (FELS) subjects to teachers from different specializations. The study recommended further qualitative research to understand the program's effectiveness better.